Is Vascular Amyloidosis Intertwined with Arterial Aging, Hypertension and Atherosclerosis? - Wang, Yushi; Feng, Xiaoxing; Shen, Botao; Ma, Jing; Zhao, Waiou (Frontiers in Genetics, 2017)
Vascular amyloidosis(VA) is a component of aging, but both VA and aging move forward together. Although not all age-related molecules are involved with VA, some molecules are involved in a crosstalk between both of them. However, the cellular mechanism by which, vascular cells are phenotypically shifted to arterial remodeling, is not only involved in aging but also linked to VA. Additionally, patients with hypertension and atherosclerosis are susceptible to VA, while amyloidosis alone may provide fertile soil for the initiation and progression of subsequent hypertension and atherosclerosis. It is known that hypertension, atherosclerosis and amyloidosis can be viewed as accelerated aging. This review summarizes the available experimental and clinical evidence to help the reader to understand the advance and underlying mechanisms for VA involvement in and interaction with aging. Taken together, it is clear that VA, hypertension and atherosclerosis are closely intertwined with arterial aging as equal partners.